UNEMPLOYMENT IN PAKISTAN: THE ROLE OF EDUCATIONAL TIERS IN DRIVING JOB MARKET OUTCOMES: UNEMPLOYMENT IN PAKISTAN: THE ROLE OF EDUCATIONAL TIERS IN DRIVING JOB MARKET OUTCOMES - Dr. Muhammad Shabbir,; Fatima Gulzar,; Sabahat Aziz Malik,; Muhammad Waseem Shahzad,; Dr. Shujahat Ali, (Dialogue Social Science Review (DSSR), 2025)
The main purpose of this study is to explore the impact of various categories of education on reducing unemployment in Pakistan over the period from 1980 to 2018. Education is widely recognized as a key driver of economic development and a critical tool for poverty reduction. The primary variable of interest in this research is educational attainment, segmented into primary, secondary, and tertiary levels. In addition, the study incorporates key control variables, including government expenditure on education and health, to provide a comprehensive understanding of the dynamics at play. To assess both the long and short-run associations among these variables, econometric techniques were employed, revealing that approximately 43% of disequilibrium adjusts toward the long-run equilibrium in each period. The Wald test was utilized to explore causal relationships among the variables. The empirical findings indicate that tertiary education plays a significantly more influential role in reducing unemployment compared to primary and secondary education, suggesting that lower levels of education alone are insufficient to tackle unemployment in Pakistan. Moreover, government expenditures on education and health were found to have a positive impact on employment generation. Based on these findings, the study recommends increased public investment in higher education and health sectors as a means to strengthen human capital, enhance employment opportunities, reduce economic inequality, and promote overall societal welfare